The Assessment of Community Participation in The Development of Marine Tourism in the Spermonde Islands - Nugroho, Fajar Aditya; Eldina, Ginta; Novanda, Nino Wahyu; Br. Ginting, Nicola Tesalonika; Putri, Regita Dwi (E-Journal of Tourism; Volume 9 Number 2 (September 2022)DO - 10.24922/eot.v9i2.89175, 2022)
As a type of mass tourism that continues to experience an increasing trend of market interest, marine tourism is a very prospective sector to be developed. Especially in its role to improve the welfare of the community in tourism destinations. This can be a solution for many areas that have marine tourism potential but the community is still not developed, such as the Spermonde Islands in Indonesia. By using quantitative descriptive research methods, measurable data in the form of public opinion on questions asked based on indicators collected, and the extent to which the Spermonde Islands community is involved in the development of marine tourism can be mapped. The results state that in general the people of the Spermonde Islands can be said to have participated in tourism activities even though they are still at a lower level. So, in the future, several strategies are needed to increase community participation. Keywords: marine tourism; community participation; community development